The means to an end: an examination of gender inequality in athletic aid distribution and graduation rates - O`Connor, P. J. (Sport in Society: Cultures, Commerce, Media, Politics, 2021)
This article examines two issues central to the interests of student-athletes and the universities that serve them, the distribution of athletic aid and graduation rates. More specifically, this article compares female and male graduation rates, and the distribution of athletic aid for 225 NCAA Division I institutions over an eight-year period between 2003 and 2010. The findings reveal two trends: First, that female athletes receive consistently and increasingly less in athletic aid than their male counterparts. Second, that while receiving comparatively and increasing less in athletic aid, female athletes graduate at significantly higher rates than male athletes as well as the female and male student body. The findings of this study are intended to be not only informative, but also prescriptive in terms of how the distribution of athletic aid and the allocation of academic support can become a more equitable and strategic means for reaching the end goal of academic achievement.